Exploring DNA Variant Segregation Types Enables Mapping Loci for Recessive Phenotypic Suppression of Columnar Growth in Apple - Dougherty, Laura; Bai, Tuanhui; Brown, Susan; Xu, Kenong (Frontiers in Plant Science, 2020)
Columnar apples trees, originated from a bud mutation ‘Wijcik McIntosh’, develop a simple canopy and set fruit on spurs. These characteristics make them an important genetic resource for improvement of tree architecture. Genetic studies have uncovered that columnar growth habit is a dominant trait and is caused by a retroposon insertion that induces the expression of the neighboring gene Co encoding a 2OG-Fe(II) oxygenase. Here we report the genetic mapping of two loci of recessive repressors c2 (on Chr10) and c3 (on Chr9) that are linked to repression of the retroposon-induced Co gene expression and associated columnar phenotype in 275 F1 progeny, which were developed from a reciprocal cross between two columnar selections heterozygous at the Co locus. The mapping was accomplished by sequencing a genomic pool comprising 18 columnar progenies and another pool of 16 standard progenies that also carry the retroposon insertion, and by exploring DNA variants of segregation types that are informative for mapping recessive traits in apple. The informative segregation types include <hk × hk>, <lm × ll>, <nn × np>, <lm × mm>, and <pp × np>, where each letter denotes one of the four DNA bases and the letters in bold represent variants in relation to the reference genome. The alleles in each first and third positions are assumed in linkage with the recessive repressors’ allele in the two parents, respectively. Using RNA-seq analysis, we further revealed that the Co gene together with the differentially expressed genes under loci c2 and c3 form a co-expression gene-network module associated with growth habit, in which 12 MapMan Bins were enriched.